2013
DOI: 10.1371/journal.pone.0068328
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine Kinase Activity Is Not Required for Tumor Cell Viability

Abstract: Sphingosine kinases (SPHKs) are enzymes that phosphorylate the lipid sphingosine, leading to the formation of sphingosine-1-phosphate (S1P). In addition to the well established role of extracellular S1P as a mitogen and potent chemoattractant, SPHK activity has been postulated to be an important intracellular regulator of apoptosis. According to the proposed rheostat theory, SPHK activity shifts the intracellular balance from the pro-apoptotic sphingolipids ceramide and sphingosine to the mitogenic S1P, thereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 21 publications
3
79
0
1
Order By: Relevance
“…both genetic ablation and SPHK inhibitors with micromolar inhibitory constants has described a role for SPHK1 in cancer cell proliferation and resistance to radiotherapy and chemotherapeutics (19,(51)(52)(53). In agreement with the results published by Kharel et al (36), Schnute et al (37), and Rex et al (38), we found that specific pharmacological inhibition of bulk S1P production by SPHK1 does not affect cancer cell proliferation and therapeutic resistance. However, SKI-1a did inhibit the angiogenic response of cocultured endothelial cells, in agreement with recent results showing an antiangiogenic effect of another SPHK1 inhibitor (41) and an inhibitory effect of SPHK1 silencing in cancer cells on the alignment of cocultured endothelial cells into tube-like structures in the two-dimensional Matrigel angiogenesis model (54).…”
Section: Discussionsupporting
confidence: 91%
“…both genetic ablation and SPHK inhibitors with micromolar inhibitory constants has described a role for SPHK1 in cancer cell proliferation and resistance to radiotherapy and chemotherapeutics (19,(51)(52)(53). In agreement with the results published by Kharel et al (36), Schnute et al (37), and Rex et al (38), we found that specific pharmacological inhibition of bulk S1P production by SPHK1 does not affect cancer cell proliferation and therapeutic resistance. However, SKI-1a did inhibit the angiogenic response of cocultured endothelial cells, in agreement with recent results showing an antiangiogenic effect of another SPHK1 inhibitor (41) and an inhibitory effect of SPHK1 silencing in cancer cells on the alignment of cocultured endothelial cells into tube-like structures in the two-dimensional Matrigel angiogenesis model (54).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, at the rat enzymes, SLC5111312 is a nonselective inhibitor. We and others have observed a similar differential in potency between mouse and human SphK1 over a variety of chemical scaffolds (Schnute et al, 2012;Rex et al, 2013;Zhang et al, 2014;Patwardhan et al, 2015). Importantly, SLC5111312 provides a tool that is simultaneously a SphK2 selective (mouse) and dual SphK (rat and human) inhibitor.…”
Section: Sphk2 and Blood S1pmentioning
confidence: 55%
“…Earlier studies with genetic models of sphingosine kinase overexpression (107) and lower potency sphingosine kinase inhibitors have suggested a potentially important role for SPHKs in tumor cell proliferation and survival (105). However, results with novel, highly potent, and selective inhibitors that reduce S1P to undetectable levels in tumor cells did not affect their growth in vitro or in vivo, suggesting that tumor sphingosine kinases may not be efficacious therapeutic targets for cancer (108)(109)(110).…”
Section: S1p In Diseasementioning
confidence: 99%